2023
DOI: 10.1002/app.53651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on flax fiber reinforced natural rubber green composite

Abstract: The present work is an attempt to study the effect of different surface treatments of flax fiber on the mechanical properties of the natural fiber reinforced natural rubber (NR) composites. In this study, flax fiber was chopped to 1, 1.25, and 1.5 cm in length and mixed with NR in two roll mill. The composite of 20%, 30%, 40%, and 50% fiber loading was prepared from each fiber length. Tensile analysis showed that a 1.25 cm fiber length composite of volume 40% has higher tensile strength compared to others.Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The enhancing effect of dynamic molding on the thermal crosslinking process was further verified through micro‐morphology comparison. According to the morphology, it can be believed that the crystalline region of cellulose was filled into modified amorphous region with favorable thermal deformability, which differed from ordinary natural fibers board and natural fibers composites with polymer 40,41 . The formed biocomposites can be regarded as a bioplastic.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancing effect of dynamic molding on the thermal crosslinking process was further verified through micro‐morphology comparison. According to the morphology, it can be believed that the crystalline region of cellulose was filled into modified amorphous region with favorable thermal deformability, which differed from ordinary natural fibers board and natural fibers composites with polymer 40,41 . The formed biocomposites can be regarded as a bioplastic.…”
Section: Resultsmentioning
confidence: 99%
“…Three replicas were taken for the test, and the average weight loss was recorded. The weight loss was taken as a measure of biodegradation of the composite (Maran et al, 2014;Samant et al, 2023). To examine the water absorption properties, the composite samples were immersed in distilled water and weighed at regular intervals.…”
Section: Characterization Of Compositesmentioning
confidence: 99%
“…Therefore, cellulose needs to be modified before filling the polymer to improve the interfacial bonding between cellulose and the polymer matrix. Several studies have reported the application of cellulose as an effective filler for rubber composites in place of commonly used fillers such as carbon black (CB) and silica 18,19 . Jiang et al 20 modified nanocrystalline cellulose (NCC) separated from softwood pulp using the cationic surfactant cetyltrimethylammonium bromide to replace a portion of CB and strengthen NR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the application of cellulose as an effective filler for rubber composites in place of commonly used fillers such as carbon black (CB) and silica. 18,19 Jiang et al 20 modified nanocrystalline cellulose (NCC) separated from softwood pulp using the cationic surfactant cetyltrimethylammonium bromide to replace a portion of CB and strengthen NR. The results showed that the tensile strength, elongation at break, tear strength and wear resistance of the modified composites were significantly improved, although the 300% tensile strength of these composites was lower, and the accumulated heat of dynamic compression fatigue was increased.…”
Section: Introductionmentioning
confidence: 99%